Changes in response time in elite taekwon-do athletes and wrestlers resulting from led lighting training - Bujak, Z.; Gierczuk, D. (Polish Journal of Sport and Tourism, 2024)
Introduction. Fighting effectiveness of combat sports athletes depends, among other factors, on response time. Athletes must react swiftly to various actions of their opponents during the combat. Understanding the determinants of response time can provide valuable insights and optimize the sports training process. The aim of this study was to determine the influence of Led Lighting Training (LLT) on response time of athletes representing extremely different combat sports.